2007
DOI: 10.1073/pnas.0702337104
|View full text |Cite
|
Sign up to set email alerts
|

ephrinB1 signals from the cell surface to the nucleus by recruitment of STAT3

Abstract: The Eph (erythropoietin-producing hepatoma) family of receptor tyrosine kinases and their membrane-bound ligands, the ephrins, have been implicated in regulating cell adhesion and migration during development by mediating cell-to-cell signaling events. The transmembrane ephrinB (Eph receptor interactor B) protein is a bidirectional signaling molecule that sends a forward signal through the activation of its cognate receptor tyrosine kinase, residing on another cell. A reverse signal can be transduced into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 49 publications
0
62
0
Order By: Relevance
“…LMO4 is a small protein (165 aa) that contains two protein-interacting LIM domains. LMO4 serves not only as a cofactor of many transcription factors (Manetopoulos et al, 2003;Kashani et al, 2006;Schock et al, 2008), but also interacts with transmembrane receptors to modulate their signaling (Novotny-Diermayr et al, 2005;Bong et al, 2007). Whether LMO4 couples signals from membrane receptors to changes in gene expression is not known, although we showed that LMO4 is present in the cytoplasm and nucleus, and translocates from the cytoplasm to the nucleus in response to extracellular stimuli (Chen et al, 2007a).…”
Section: Introductionmentioning
confidence: 73%
“…LMO4 is a small protein (165 aa) that contains two protein-interacting LIM domains. LMO4 serves not only as a cofactor of many transcription factors (Manetopoulos et al, 2003;Kashani et al, 2006;Schock et al, 2008), but also interacts with transmembrane receptors to modulate their signaling (Novotny-Diermayr et al, 2005;Bong et al, 2007). Whether LMO4 couples signals from membrane receptors to changes in gene expression is not known, although we showed that LMO4 is present in the cytoplasm and nucleus, and translocates from the cytoplasm to the nucleus in response to extracellular stimuli (Chen et al, 2007a).…”
Section: Introductionmentioning
confidence: 73%
“…In light of these reports, it is not unreasonable to believe that higher levels of TIMP2 and lower levels of TIMP3 transcripts are mediators of similar phenotypic effects in EphB6-transfected MDA-MB-231 cells. The mechanism of MMP and TIMP transcriptional regulation is not clear; however, it has been shown that Eph receptors (Lai et al, 2004) and ephrin ligands (Bong et al, 2007) can transduce signals to the nucleus through the Jak/STAT pathway. In addition, EphB6 is capable of suppressing signaling through the JNK pathway in T-cell development following stimulation with ephrinB1 (Freywald et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The bidirectional signaling molecule ephrin-B2 becomes clustered upon interaction with its Eph receptor 37 and activates key signaling moieties such as Src, 28 PDGFRβ, 37 VEGFR2, 38 STAT3, 39 and many more. Until date, only one study has reported the involvement of Eph-ephrin signaling in conferring radioresistance, but the mechanism is poorly understood.…”
Section: Discussionmentioning
confidence: 99%